2009
DOI: 10.2337/dc08-1722
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function Is Disrupted by Both Hypo- and Hyperglycemia in School-AgedChildren With Type 1 Diabetes: A Field Study

Abstract: OBJECTIVEWe developed a field procedure using personal digital assistant (PDA) technology to test the hypothesis that naturally occurring episodes of hypo- and hyperglycemia are associated with deterioration in cognitive function in children with type 1 diabetes.RESEARCH DESIGN AND METHODSA total of 61 children aged 6–11 years with type 1 diabetes received a PDA programmed with two brief cognitive tests (mental math and choice reaction time), which they completed just before home glucose readings. The computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
1
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 16 publications
4
101
1
8
Order By: Relevance
“…However, the literature also indicates results in favor of the relationship between the variable Glycemic Control and presence of cognitive impacts, noting that better performances are shown in specific cognitive domains by subjects with Appropriate Glycemic Control (Gonder-Frederick et al, 2009;Knight et al, 2009;Parent, Wodrich & Hasan, 2009;Patiño-Fernández et al, 2010). It is noteworthy that in the studies reviewed there are no results in favor of the group with Inappropriate Glycemic Control, exactly as was observed in this study.…”
Section: Discussionsupporting
confidence: 71%
“…However, the literature also indicates results in favor of the relationship between the variable Glycemic Control and presence of cognitive impacts, noting that better performances are shown in specific cognitive domains by subjects with Appropriate Glycemic Control (Gonder-Frederick et al, 2009;Knight et al, 2009;Parent, Wodrich & Hasan, 2009;Patiño-Fernández et al, 2010). It is noteworthy that in the studies reviewed there are no results in favor of the group with Inappropriate Glycemic Control, exactly as was observed in this study.…”
Section: Discussionsupporting
confidence: 71%
“…Hyperglycemia may be one of the reasons for different drug effects between the healthy and diabetic groups. Several studies in humans or animals have reported cognitive and memory function impairment in hyperglycemia [56, 57]. These deficits induced by hyperglycemia are underlined by cholinergic dysfunction (due to increased acetylcholinesterase activity) [58] and reactive oxygen species production due to accelerated respiration (mitochondrial oxidative metabolism of glucose), which in turn increases oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more frequent monitoring may be needed over the next 24 hours due to increased risk of delayed hypoglycemia especially until the individual's glycemic response pattern to exercise is well defined (31,34). Optimal sports performance particularly in activities requiring the highest focus and precision would be expected when glycemic control is in a reasonably normal range as cognitive function and "mental efficiency" have been shown to be relatively lower during periods of hypoglycemia or significant hyperglycemia (35).…”
Section: Blood Glucose Monitoringmentioning
confidence: 99%